Effect of National Senior Certificate maths on the pass rate of first-year Engineering physics - Jagathesan Govender; Mervlyn Moodley (South African Journal of Science, 2012)
There has been much controversy about the mathematics results of the 2008 National Senior Certificate examinations - the first to be written by pupils following the outcomes-based curriculum. This article examines the impact of the new high school mathematics curriculum on the performance in physics by first-year Engineering students at the University of KwaZulu-Natal. The first-year physics results of the Engineering students who wrote the 2008 National Senior Certificate (NSC) examinations were compared with the physics results of the Engineering students of the previous 4 years who wrote the Senior Certificate Examinations (SCE). Analysis of variance was used to compare the average physics marks of the NSC and SCE groups. Correlation analysis was performed to determine the relationship between performance in high school mathematics with performance in first-year physics in Engineering for both the 2008 NSC group and the 2007 SCE group. The results showed a lower physics pass rate for the NSC students compared with that of the SCE students. There was also a significant difference in the average marks obtained in physics between the NSC students and the SCE students. The new high school mathematics curriculum has fallen short in providing essential skills and techniques for students who wish to study physics at university. Furthermore, the high school mathematics results of the NSC students are an indication of considerable grade inflation.